Agreement between 3D Motion Analysis and Tele-Assessment Using a Video Conferencing Application for Telerehabilitation - Kyeongjin Lee (MDPI AG, 2021)
The global pandemic of the coronavirus disease 2019 (COVID-19) has highlighted the need for remote healthcare services. This study aimed to evaluate the concurrent validity and reliability of tele-assessment using 3D motion analysis and video conferencing applications. The subjects of this study were 14 Pilates instructors and 14 healthy adults, who repeated five exercises of “side spine stretch”, “bridge”, “toe taps”, “quadruped leg raise”, and “cat and cow” five times each. We performed 3D kinematic analysis with 16 infrared cameras while the subject performed each exercise, and the image captured by one webcam was transmitted to the evaluators through a video conferencing application, and eight raters evaluated the mobility, stability, and symmetry of the movement. The result was then compared with the gold standard 3D motion analysis to evaluate the teleassessment system. The concurrent validity of the data obtained using both methods was analyzed. In addition, the inter-rater reliability of the data from the eight raters was evaluated. As a result, mobility showed excellent (ICC > 0.75, ICCs: intraclass correlation coefficients) or good agreement (ICC = 0.6–0.74) with 3D motion analysis and tele-assessment in all motions. The analysis of stability showed high agreement in general, but it was not significant in “cat and cow.” Symmetry showed moderate agreement only in “bridge” and “toe taps”, showing low agreement compared to other components. In addition, the inter-rater reliability of the tele-assessment showed good agreement (ICC = 0.744). Although there were few components with weaker agreements, the results of this study confirmed that it is a valid and reliable method of tele-assessment using video conferencing applications and showed feasibility as an alternative to the existing face-to-face examination.